ASSESSMENT OF MALATHION TOXICITY IN CERTAIN ORGANS OF EARTHWORM, EISENIA FOETIDA - K. BANSIWAL; N. RAI (The Bioscan, 2010)
The present study reveals the toxic effects on integument and ventral nerve cord of Eisenia foetida after treatment of Malathion. A higher sub lethal dose of Malathion (3/4th of LD50 that is 16000mg/Kg soil) was used to evaluate the toxicity of Malathion on the integument and ventral nerve cord. These changes include ruptured cuticle, deformed circular and longitudinal muscles in integument and distorted ventral nerve cord. It is suggested that Malathion at 12000mg/Kg soil for 96 hr has caused histopathological changes in integument and ventral nerve cord that will ultimately affect the proper functioning of E. foetida. Thus it can be said that Malathion is not only a neurotoxin agent.